ZAKAT DALAM ISLAM SEBAGAI AKTIVITAS IBADAH SOSIAL - Achmad Yaman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This study analyzes zakat in Islam and its relation as a social worship activity. This research discourse uses qualitative research with a literature study approach. Sources of library data used are from the Qur'an, books of interpretation, hadith, journals, and research published online. The data analysis method used is data reduction, data display, and drawing conclusions. The nature of the data analysis used is descriptive analytical. The conclusion of the study is that Zakat is a maliyah worship and is included in the five pillars of Islam, therefore zakat is the foundation of Islam, besides being an obligation for a Muslim, it is also fully realized that zakat is a key instrument in growing and improving the social life of the people, with its big role. able to become a social glue tool and cut the distance between the rich and the poor as well as minimize social inequality and furthermore can be an important element of preventing crime in the midst of society